'Oh,' 'Well,' and Hedges as Negative Politeness Strategy: The Different Use of Discourse Markers in Female and Male Students' Utterances - Ratna Padmi Trihartanti; Muchammad Yassin Fadilah (IAIN MADURA, 2022)
Investigating gender differences in utterances by employing discourse markers is very interesting and challenging as the similarities and differences could be seen more distinctly than without them. This research aims to find out the similarities and the differences between them in students’ interactions. The data were taken from female and male students’ utterances. After being analyzed using the qualitative method, it concluded that there were some similarities and differences in applying them. For expressing hesitation, Female students use ‘Hmm…,’ (20%), ‘I think…,’ (17%), and ‘Well…,’ (15%). Meanwhile, male students use ‘Well…’ (19%), ‘I think...,’ (20%), and ‘Hmm…,’ (10%). Female students use ‘Well…’ as a face threat mitigator and sometimes followed by ‘sorry …,’ (12%), whereas male students employ ‘Well…’ (7%). For expressing surprise, both use ‘Oh’ as a pure surprise (9%) and (6%). Female students prefer to use discourse markers ‘Wow…,’ (7%) if they feel amazed, whereas male students apply ‘Aah…,’ (6%). Both female and male students employ ‘By the way…,’ to interrupt (8%). The research revealed that male students hide their doubts better than female students; female students are more polite. The research also finds discourse markers from students’ local language that could be developed globally.